Does sodium nitroprusside kill babies? A systematic review - Sass, Nelson (2007)
OBJECTIVE: To determine whether sodium nitroprusside causes fetal death in pregnancies complicated with hypertension. DATA SOURCES: Medical Literature Analysis and Retrieval System Online (MEDLINE; 1996 to 2003), Excerpta Medica (EMBASE; 1970 to 2003), Web of Science/Institute for Scientifi c Information (ISI; 1945 to 2003), Literatura Latino-Americana e do Caribe em Ciências da Saúde (LILACS; 1982 to 2003) and the Cochrane Library. REVIEW METHODS: The medical subject headings used were “nitroprusside and pregnancy”, “hypertension or eclampsia or preeclampsia” and “nitroprusside and pregnancy and hypertensive emergencies”. The search was limited to humans and female gender, in all fi elds, publication types, languages and subsets. Articles were also identifi ed by reviewing the references of articles and textbooks on hypertension and pregnancy. RESULTS: The search located nine studies. The sum of all the publications yielded a total of 22 patients and 24 exposed fetuses (two pairs of twins). There were no randomized clinical trials and no prospective cohorts. All of the studies were observational in nature. CONCLUSIONS: At present, there is insuffi cient evidence for defi nitive conclusions about any direct association between sodium nitroprusside use and fetal demise.